Holocene sea level and climate interactions on wet dune slack evolution in SW Portugal: A model for future scenarios?. (January 2019) - Leira, Manel; Freitas, Maria C; Ferreira, Tania; Cruces, Anabela; Connor, Simon; Andrade, Cesar; Lopes, Vera; Bao, Roberto
We examine the Holocene environmental changes in a wet dune slack of the Portuguese coast, Poço do Barbarroxa de Baixo. Lithology, organic matter, biological proxies and high-resolution chronology provide estimations of sediment accumulation rates and changes in environmental conditions in relation to sea-level change and climate variability during the Holocene. Results show that the wet dune slack was formed 7.5 cal. ka BP, contemporaneous with the last stages of the rapid sea-level rise. This depositional environment formed under frequent freshwater flooding and water ponding that allowed the development and post-mortem accumulation of abundant plant remains. The wetland evolved into mostly palustrine conditions over the next 2000 years, until a phase of stabilization in relative sea-level rise, when sedimentation rates slowed down to 0.04 mm yr −1, between 5.3 and 2.5 cal. ka BP. Later, about 0.8 cal. ka BP, high-energy events, likely due to enhanced storminess and more frequent onshore winds, caused the collapse of the foredune above the wetlands' seaward margin. The delicate balance between hydrology (controlled by sea-level rise and climate change), sediment supply and storminess modulates the habitat's resilience and ecological stability. This underpins the relevance of integrating past records in coastal wet dune slacks management in a scenario of constant adaptation processes.